Use of a 3D Model for the Correction of a Complex Madelung Deformity in a Teenager: A Case Report. Issue 2 (13th April 2022) - Catena, Nunzio; Arrigoni, Chiara; Origo, Carlo
Abstract : Case: The aim of the article is to report on a case of a teenager affected by Madelung deformity treated with a double osteotomy, planned by means of a 3D model. Using a custom-made cutting guide, the radial osteotomy was performed, and after the reorientation, a shortening ulnar osteotomy completed the procedure. Postoperative clinical assessment showed a normal alignment of the ulna with increased range of motion wrist motion. Conclusions: Using a 3D model when planning a multidirectional correction of a Madelung deformity may be advantageous to achieve a more accurate and precise realignment of the carpus and distal radioulnar joint.